Efek Suhu Ekstraksi Kunyit dan Penggabungan Minyak Sawit Dalam Aplikasi Pembuatan Sabun Transparan Sebagai Media Perlindungan Kulit - Gunawan, Desdy H; Mangunsong, Lamria (Politeknik Negeri Pontianak, 2022)
The research is based on the need for natural ingredients that are protective for skin health to avoid infection. Considering that currently there is a dangerous outbreak caused by a virus, so it is very necessary to protect it in various preparations that are easy to use, such as soap. The purpose of the study was to determine the effect of the combination of palm oil and turmeric extract extracted with different temperature variations on the resulting transparent soap. The stages of this research have 3 main stages, namely 1) Making turmeric extract with temperature variations of 50.55 and 60oC for 15 minutes, 2) Making transparent soap with a formulation of turmeric extract and palm oil 3) Physical and chemical analysis of the resulting transparent soap. The test results concluded that the soap did not cause skin irritation, the range of alkaline pH was 9.5-9.6 and the foam stability was relatively maintained from all samples, the water content was below 15% and the ALB was carried 2.5% and the physical properties in the form of a soap hardness texture that did not shrink quickly. destroyed during use.